Saccharomyces cerevisiae oxidative response evaluation by cyclic voltammetry and gas chromatography−mass spectrometry - Castro, Cristiana C. (2012)
This study is focused on the evaluation of the impact of Saccharomyces cerevisiae metabolism in the profile of compounds with antioxidant capacity in a synthetic wine during fermentation. A bioanalytical pipeline, which allows for biological systems fingerprinting and sample classification by combining electrochemical features with biochemical background, is proposed. To achieve this objective, alcoholic fermentations of a minimal medium supplemented with phenolic acids were evaluated daily during 11 days, for electrochemical profile, phenolic acids, and the volatile fermentation fraction, using cyclic voltametry, high-performance liquid chromatography-diode array detection, and headspace/solid-phase microextraction/gas chromatography-mass spectrometry (target and nontarget approaches), respectively. It was found that acetic acid, 2-phenylethanol, and isoamyl acetate are compounds with a significative contribution for samples metabolic variability, and the electrochemical features demonstrated redox-potential changes throughout the alcoholic fermentations, showing at the end a similar pattern to normal wines. Moreover, S. cerevisiae had the capacity of producing chlorogenic acid in the supplemented medium fermentation from simple precursors present in the minimal medium.